If You Can't Trust Your Mother, Who Can You Trust? : Soul Murder, Psychoanalysis, and Creativity - Shengold, Leonard (Karnac, 2013)
The main theme of this book concerns the continuing psychic centrality of parents for their children. Several chapters examine an author and his works, outlining that author's relationships with parents, good-and-bad, and making descriptive comments about these based both on information gleaned from the author's life and writings as well as from observations found in autobiographies, biographies and critical works. Since these studies in part concern stories of child abuse and deprivation, the book predominantly illustrates bad parenting that seems to have contributed to the child's psychopat.